Entrepreneurial ecosystem: Analysis of the contribution of universities in the creation of technology-based firms - Silva, João Paulo Moreira; Guimarães, Liliane de Oliveira; Inácio Júnior, Edmundo; Castro, José Márcio de (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
This paper aimed to analyze how higher education institutions contribute to the creation of technology-based firms. The research method was that of multiple cases, represented by two universities and five technology-based firms in Belo Horizonte. We selected businesses that had as founders students or former students of the researched universities. The results showed that the institutions have robust structures and programs, but still act in a little internally integrated way. In addition, the entrepreneurs do not identify the contribution of their university education in their entrepreneurial trajectory. The study contributes to the understanding of the role of the university in the entrepreneurial ecosystem. From a theoretical point of view, the study identified categories of analysis to evaluate entrepreneurial universities.